Tinjauan Kehalalan Produk Susu Etawa: Studi Kasus HALT Corpora - Rosalina, Siti; Shidqi, Muhammad Azam (Journal of Fiqh in Contemporary Financial Transactions, 2024)
This research aims to evaluate the compliance of the production and distribution processes at CV. Halt Corpora with the regulations stipulated in Law Number 33 of 2014 concerning Halal Product Assurance. The research method employed is field research, focusing on the owner and Production Chairperson of CV. Halt Corpora as the research subjects. Data were collected through interviews, observations, and documentation, and subsequently analyzed descriptively. The results indicate that the production and distribution processes at CV. Halt Corpora adhere to the principles of Islamic Economic Law and Law Number 33 of 2014 concerning Halal Product Assurance. However, attention should be given to aspects such as justice, honesty, and transparency in transactions, as well as maintaining public trust. The presence of the MUI Halal Certificate signifies compliance with halal principles, but special attention is needed regarding the extension and renewal of the certificate to preserve and enhance consumer confidence in the produced products.